Diagnostic Accuracy of Doppler Ultrasound in Testicular Torsion Keeping Surgical Findings as the Gold Standard - Shafi, Aqeel; Zameer, Shahla; Liaqat, Bushra; Liaqat, Rabia; Riaz, Ramish; Liaqat, Maria (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of ultrasound with Doppler analysis in testicular torsion, keeping surgical findings as the gold standard.Study Design: Cross-sectional validation studyPlace and Duration of study: Radiology Department of Pakistan Institute of Medical Sciences, from Dec 2017 to Dec 2019.Methodology: The study included 58 candidates of acute scrotum who were clinically equivocal with a strong suspicion of testicular torsion and were referred by the concerned surgery department to Radiology, where a senior resident performed the testicular ultrasound. The grey scale features, along with doppler findings, were noted. Only those cases that underwent surgical exploration were included. The clinical, sonological, and per-operative findings were recorded.Results: The mean age of our study was 18.00±6.02 years. The sensitivity, specificity, positive predictive value and negative predictive value of Doppler ultrasound were 98%, 86%, 98% and 86%, respectively. The most consistent Doppler ultrasound feature was absent intra-testicular flow, found among 46 out of 50 surgically confirmed cases of testicular torsion, while four had reduced intra-testicular flow. Similarly, heterogeneous testicular echotexture was the most frequently met grey scale feature. The sonological Whirlpool sign in our study came had 69% sensitivity and 100% specificity.Conclusion: The overall diagnostic accuracy of ultrasound is significantly high, especially when both greyscale and colour Doppler findings are simultaneously interpreted. The sensitivity of ultrasound in diagnosing testicular torsion is far more than its specificity.